Challenges facing the former mono-industrial communities: unemployment, lack of investments - a study on Roşia Montană = Wyzwania stojące przed byłymi społecznościami monoprzemysłowymi: bezrobocie, brak inwestycji - badanie na temat Roşia Montană - Mucea, Bogdan-Nicolae (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to present the opinions of the inhabitants of the Romanian local community Roşia Montană, who are coping with challenges arising from the closure of mining investments. The analysis focuses on prevalent challenges affecting populations of former mining communities, namely high unemployment rate and poverty.
Keywords: unemployment; poverty; mono-industrial area; Roşia Montană; community investment; bezrobocie; ubóstwo; obszar monoprzemysłowy; inwestycja społeczna